Osteosarcopenia - James Paintin; Cyrus Cooper; Elaine Dennison (2018)
Osteosarcopenia is a newly described syndrome that describes the co-existence of osteoporosis and sarcopenia, two chronic musculoskeletal conditions associated with ageing. Osteoporosis, a condition of low bone mass and micro-architectural deterioration of bone, and sarcopenia, the loss of muscle mass, strength and function, often co-exist in a frail subset of the elderly population, leading to significantly worsened outcomes than seen in either condition alone. These include a greater risk of falls, fractures and institutionalization, and significant socioeconomic costs. With our ageing population, osteosarcopenia is a public health concern that will become increasingly relevant in the future. Its aetiology is multifactorial, with mechanical, biochemical, genetic and lifestyle factors all contributing to involution of the ‘bone–muscle unit’. Improved understanding of the interactions between muscle and bone could facilitate the development of new therapeutic agents which target muscle and bone as one. Together with existing pharmacological, nutritional and exercise-based therapies, this should enable a more holistic approach to osteosarcopenia in the future.